Isolating and culturing of sputum macrophages: A potential ex vivo/in vitro model. (3rd July 2018) - Bølling, Anette Kocbach; Steensen, Tonje Berg; Alexis, Neil E.; Sikkeland, Liv Ingunn Bjoner
Abstract: Purpose: This paper aimed to test whether induced sputum samples acquired from human volunteers could be used to isolate and culture airway macrophages for in vitro exposures. This was assessed in terms of the culturing success rate, culture purity, viability and responsiveness of cultured cells.Materials and methods: The isolation and culturing procedure was performed over three days. On Day 1, induced sputum samples were obtained, processed and seeded in culture wells. Differential cell counts and viability tests were performed to allow for calculation of viable macrophage numbers and appropriate sample dilution. After a 1 h rest, seeded wells were washed to remove non-adherent cells, resulting in macrophage isolation. Then, cells rested overnight (Day 1–Day 2), before in vitro exposure for 2–24 h (Day 2–Day 3). The criteria for progressing into the culturing procedure was cell viability >40% and total cell number >10 6 . Successful culturing was evaluated based on cell attachment ( N = 40). Culture purity by differential cell analysis and viability was monitored during culturing ( N = 4–8). Macrophage responsivity was assessed by measurement of inflammatory cytokine gene expression ( N = 4) and cytokine levels ( N = 6) following in vitro exposure to lipopolysaccharide (LPS) (2–24 h) and live bacteria ( S. aureus ) (4h).Results: Overall, 88% (35/40) of the samples acquired were suitable for isolation, and 80% (32/40) were successfully progressed through the 2–3 day culturing protocol. Macrophage purity (88%) and viability (85%) were adequate. Moreover, cultured macrophages were responsive to in vitro stimulation with LPS and viable S. aureus showing positive mRNA responses for TNFα, IL-1β and IL-8 and release of IL-1β, respectively.Conclusion: Sputum macrophage isolation by plate adherence and subsequent culturing of sputum macrophages was successfully performed and represents a promising in vitro model for examination of airway macrophage behavior.